Work and Family Roles of Soviet Women: Historical Trends and Cross-Section Analysis - Ofer, Gur; Vinokur, Aaron (Journal of Labor Economics, 1985)
Over the last two generations, women in Soviet Russia reached the highest labor force participation rate in the world. As everywhere else, the process was accompanied by a sharp rise in their educational attainment and a similarly sharp decline in fertility. On the basis of data about families of Soviet emigrants during the early 1970s, it is shown that Soviet women respond to the same economic variables that create similar trends in market economies. Socialist ideology and Soviet growth strategy help on the one hand to expedite the process, but on the other amplify the contradiction between women's family and labor market roles and result in relatively low wages for women.